A case of primary diffuse large B‐cell non‐Hodgkin's lymphoma misdiagnosed as chronic periapical periodontitis. (5th May 2013) - Jessri, M; Majeed, AA Abdul; Matias, MA; Farah, CS
Abstract Lymphoma is a malignant neoplasm of component cells of the lymphoid system which is very rare in the jaws. Here we report a case of primary diffuse large B‐cell lymphoma located in the periapical region of a mandibular molar which was misdiagnosed as chronic periapical periodontitis. The present case was diagnosed at an early stage and effectively managed by chemotherapy. Although lymphoma of the mandible is rare, it must be considered in the differential diagnosis of radiolucent lesions in this region. Lack of knowledge of this rare presentation may lead to delays in diagnosis and poor prognosis.